2020
DOI: 10.1002/cctc.202001527
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Promotional Effect of Cerium in the Dry Reforming of Methane

Abstract: A series of Ni‐Ce catalysts supported on SBA‐15 has been prepared by co‐impregnation, extensively characterized and evaluated in the carbon dioxide reforming of methane (DRM). The characterization by TEM, XRD and TPR has allowed us to determine the effect of metal loading on metal dispersion. Cerium was found to improve nickel location inside the mesopores of SBA‐15 and to suppress coke formation during the DRM reaction. The analysis by XPS allowed us to associate the high cerium dispersion with the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 77 publications
(127 reference statements)
2
7
0
Order By: Relevance
“…The peak A at low temperature is attributed to the reduction of the bulk NiO at the catalyst core 18,22,23 . While the peak B at high temperature is assigned to the reduction of the NiO at the catalyst core–shell interface, which may have an interaction between silica shell 18,22,23 . With increasing the amount of cerium, the area of the reduction peak B gradually increases along with the decrease of peak A, indicating that the addition of cerium enhances the dispersion of nickel oxide, which is consistent with the XRD results, so that more nickel oxide can interact with the shell layer.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The peak A at low temperature is attributed to the reduction of the bulk NiO at the catalyst core 18,22,23 . While the peak B at high temperature is assigned to the reduction of the NiO at the catalyst core–shell interface, which may have an interaction between silica shell 18,22,23 . With increasing the amount of cerium, the area of the reduction peak B gradually increases along with the decrease of peak A, indicating that the addition of cerium enhances the dispersion of nickel oxide, which is consistent with the XRD results, so that more nickel oxide can interact with the shell layer.…”
Section: Resultssupporting
confidence: 83%
“…With increasing the content of Ce species, the grain size gradually decreases to the minimum value of 6.1 nm when the Ni/Ce ratio is 10. The size of NiO particles is significantly reduced with the increase of cerium doping, indicating that cerium served as the structural promoters, which was also mentioned by the previous literature 18–21 …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Among many oxide supports, CeO 2 is a promising material with stable sites for the incorporation of Pd nanoparticles. Moreover, recent studies have highlighted its promotional effect in the DRM reaction . Ceria redox chemistry has been extensively evaluated, where several studies have identified the role of oxygen and hydrogen within the fluorite lattice. The barriers associated with the two slowest reaction steps to methane dissociation, CH 4 → CH 3 + H and CH → C + H, have been previously studied using density functional theory (DFT) methods on Pd substrates.…”
Section: Introductionmentioning
confidence: 99%
“…There are also a few experimental and theoretical studies investigating the role of low‐coordinated Ce in catalysis. Rodriguez‐Gomez et al [23] . reported that the low‐coordinated Ce atoms being exposed on the Ni−Ce catalyst are responsible for the high activity of this catalyst in the dry reforming of methane.…”
Section: Introductionmentioning
confidence: 99%